(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the frequency, indications, maternal morbidity and mortality associated with obstetrical hysterectomy. Study Design: Descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the Department of obstetrics and Gynecology KMC, Khairpur Mir’s from August 2014- July 2017. Materials and Methods: All patients operated for obstetrical hysterectomy during study period included in study. This was a retrospective study. Data was collected from yearly maintained registers on proforma. The parameters analyzed were age, parity, indications, morbidity & mortality by SPSS V- 21. Results: Total deliveries during study period were 17101. Total number of obstetrical hysterectomy during study period was 75 cases. This giving an incidence of 0.43% that is 1 in 228 deliveries. Mainly 38 (50.6%) patients were belongs to age group 30 - 40 years. 64 (85%) women were multi parous and only 11 (15%) were primigravida. Most common indication of obstetrical hysterectomy was morbid adherent of placenta (33.3%) than ruptured uterus (30.6%), abruptio placentae (18.6%), uterine atony (16%) and secondary PPH (1.3%). Regarding intra operative complication 2 (2.6%) got bladder injury. 1(1.3%) patients needed repeat laprotomy due to bleeding. 32(42.6%) patients developed post operative pyrexia, 12(16%) developed wound infection, 10 (13.3%) patients developed post operative paralytic ileus. 24 (32%) patients required ICU admission. 3 (4%) patients died due to excessive haemorrhage. 1 (1.3%) developed vesicovaginal fistula. Conclusion: The study conclude that multiparity is the risk factor for obstetrical hysterectomy. Morbid of adderentof placenta is the commonest indication due to rising trends of caesarean section. It is necessary obstetrician should avoid unnecessary cesarean section in primigravida.